2016
DOI: 10.1038/nchembio.2200
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for precursor protein–directed ribosomal peptide macrocyclization

Abstract: Macrocyclization is a common feature of natural product biosynthetic pathways including the diverse family of ribosomal peptides. Microviridins are architecturally complex cyanobacterial ribosomal peptides whose members target proteases with potent reversible inhibition. The product structure is constructed by three macrocyclizations catalyzed sequentially by two members of the ATP-grasp family, a unique strategy for ribosomal peptide macrocyclization. Here, we describe the detailed structural basis for the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
111
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(119 citation statements)
references
References 46 publications
7
111
0
1
Order By: Relevance
“…2C). While many RiPP leader peptides have been shown to adopt α-helical conformations in trifluoroethanol, the persistence of this secondary structure upon binding to the tailoring enzyme has only been observed in our structures and the recent structure of MdnC, which binds the leader peptide as a single-turn α-helix but lacks sequence homology to a typical RRE (3,9,11,28).…”
Section: Resultsmentioning
confidence: 81%
“…2C). While many RiPP leader peptides have been shown to adopt α-helical conformations in trifluoroethanol, the persistence of this secondary structure upon binding to the tailoring enzyme has only been observed in our structures and the recent structure of MdnC, which binds the leader peptide as a single-turn α-helix but lacks sequence homology to a typical RRE (3,9,11,28).…”
Section: Resultsmentioning
confidence: 81%
“…It has been shown that only a limited region of the leader peptide in many RiPPs is required for efficient modification of the precursor peptide . We investigated which region of the leader peptide is critical for the crosslinking reaction with TgnA‐R1, which was used as a model peptide.…”
Section: Resultsmentioning
confidence: 99%
“…The sortase class of enzymes, which catalyze transpeptidation by recognizing a C-terminal LXPTG motif 17 , the butelase enzyme, which is an asparagine/aspartate (Asx) peptide ligase 18 , the NRPS thioesterases 19 and the prolyl oligopeptidase (POP) class of enzymes. A further important class of macrocyclases is that of the ATP-grasp superfamily, which as the name suggests rely on ATP hydrolysis to drive macrocycliation 20 . The enzymes that catalyze close to traceless peptide bond formation regardless of the peptide sequence—, i.e., only one residue from the precursor peptide recognition tag is carried over to the final cyclic product—are PatGmac family members, butelase, and POP macrocyclases.…”
Section: Introductionmentioning
confidence: 99%